Kepercayaan Dan Praktik Shinto Dalam Anime Noragami - Brafangestu Candra Desfiyadin Nugraha; Idah Hamidah; Diana Puspitasari (KIRYOKU, 2021)
The aim of this research is to describe beliefs and Shinto practices in the anime Noragami based on the concept of religion by Koentjaraningrat and references from Danamdjaja, Nadroh and Azmi. The method used in this research is descriptive qualitative, the data collection technique used was a note-taking technique. The data used are dialogues and screenshots. The data analysis technique was carried out by analyzing the dialogue in the anime noragami related to beliefs or Shinto practices. Found three concepts of beliefs from the anime include beliefs in the existence of God, belief in the soul(spirit) of the dead, and belief in the evil spirit (ghost or monster). While Shinto rites were found, three practices include purification, offerings to gods and praying. The conclusions of this study about Japanese people’s beliefs contained in the anime Noragami in the form of supernatural and soul (spirit) concepts. For Shinto practices focus on purity, impurity and then ask God